Pengaruh Pemberian Ekstrak Daun Pepaya (Carica papaya Linn) dan Kunyit (Curcuma domestica) Terhadap Fermentabilitas Rumen Sapi Perah Secara In vitro - Annisa Ramandhani; Dian Wahyu Harjanti; Anis Muktiani (Faculty of Animal Science, Universitas Brawijaya, 2018)
This research was conducted to determine the effect of using papaya leaves extract, turmeric extract and the combination on ruminal pH, the concentrations of amonia (NH3), Volatile Fatty Acids (VFA), Acetate, Propionate, Butyrate, Methane (CH4), CO2 and Total Protein. The material was used rumen fluid of dairy cows, papaya leaves extract and turmeric extract. The study was arranged in a completely randomized design with 4 treatments and 4 replications. The treatment was control diet (T1); control diet supplemented with 0.005 ml papaya leaves extract (T2); control diet supplemented with 0.005 ml turmeric extract (T3) and control diet supplemented with 0.0025 ml papaya leaves extract and 0.0025 ml turmeric extract (T4). The rumen fluid was analyzed after 3 hours fermentation. Data were analyzed using ANOVA and continued by Duncan test. The result showed that single supplementation of either papaya leaves or turmeric extract alone and supplementation of both herbal did not affect ruminal pH, NH3, CO2 and total protein production. Moreover, there were an increase in concentrations of total VFA, acetate, propionate, butyrate and methane. The combination of papaya leaves and turmeric extract supplementation resulting in the highest concentrations of VFA (445 mMol/l), acetate (13.5 mMol/l), propionate (4.24 mMol/l), butyrate (1.87 mMol/l) and CH4 (17.17%) in the rumen. In conclusion, supplementation of papaya leaves and turmeric alone, and the combination of both herbal could enhance rumen fermentability of dairy cow.